ONLINE MOTHER SUPPORT GROUP: THE NEW WAY OF PEER SUPPORT FOR IMPROVING BREASTFEEDING PERFORMANCE - Dewanti, Lintang Purwara; Februhartanty, Judhiastuty; Roshita, Airin (JHE (Journal of Health Education), 2019)
Background: Data from Riskesdas in 2010 showed that family living in the urban area still had lower rate of exclusive breastfeeding, specifically 25.2% compare to those living in the rural area. In Jakarta, the proportion of children aged 0-23 months that still being breastfed was only 70.3%, this rate was below the national level of children age 0-23 months that still being breastfed which reach 80.1%. This study aimed to explore the experiences of mothers attending online Mother Support Group as their breastfeeding support. Methods: Qualitative approach was used to explore mothers? breastfeeding performance and mothers? experience attending the online group. Key findings show the mothers in the group exposure received support and knowledge from other mother or peers. Type of support given to the mother by both peers and experts (professionals) can be in the form of support group and given in online form. Results: There were also mothers experienced overwhelmed with the information that circulate. This kind of mothers considered that they better learning with individual setting to be more focus or conduct only virtual meeting Conclusion: Good performance on breastfeeding among mothers? can be maintained by their experiences of group that allow mothers learn in conducive environment and/or solved mothers? breastfeeding problem.